Analysis of Recruitment Methods in Employee Placement at the Civil Service and Human Resources Development Agency (BKPSDM) of Gunungsitoli City - Gulo, Joharman Ardita; Mendrofa, Syah Abadi; Zega, Yamolala; Waruwu, Meiman Hidayat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Recruitment is the process of attracting individuals as needed at the right time, in sufficient numbers, with specified qualifications, and encouraging them to apply for work with the organization. recruitment at BKPSDM must be in accordance with the needs that will be obtained after carrying out workload analysis and position analysis. Placement is placing employees as elements of work implementation in positions that are in accordance with the criteria, abilities, skills and expertise. This research was carried out at the BKPSDM office in Gunungsitoli city, the research method used was a qualitative research method. Data sources were obtained through observation, interviews and documentation. The research results show that the recruitment method at BKPSDM uses an open method, employee placement is based on academic achievement, educational background, experience, physical health, mental health, marital status and age. In general, recruitment and placement methods were carried out well. However, in placements there are still employees who are placed who do not match their educational background. The recommendation made is rotation of positions. It is hoped that the results of this research will be used as input in making policies, especially regarding the analysis of recruitment methods in employee placement at BKPSDM Gunungsitoli City.